Pricing of irrigation water and valuation of irrigation induced land, degradation effects in Kabini command, Karnataka - Shankar, K. (Team of Excellence in Natural Resource Economics, National Agricultural Technology Project, Dept. of Agricultural Econ., U. of Agricultural Sciences, 2003)
With reference to Karnataka, India.